Injuries in alpine summer sports - types, frequency and prevention: a systematic review - Sebastian Frederick Bigdon; Verena Hecht; Paul Gilbert Fairhurst; Moritz C. Deml; Aristomenis K. Exadaktylos; Christoph E. Albers (BMC, 2022)
Abstract Introduction Summer alpine sports, including mountain biking, hiking and airborne pursuits, have experienced a recent surge in popularity. Accordingly, trauma associated with these activities has increased. There is a scarcity of literature exploring clinical aspects surrounding injuries. Specifically, no single article provides a general overview, as individual studies tend to focus on one particular sport. In the present study, we performed a systematic literature review to summarize existing knowledge and explore the potential for prevention and clinical decision making in this group. Method Literature searches were performed using the PubMed and Scopus database for the most commonly ventured sports associated with injury: mountain biking, climbing, airborne sports, paragliding, and base jumping. From this search, studies were identified for qualitative and quantitative analyses. These searches were done according to PRISMA guidelines for systematic reviews. Studies were then analyzed regarding epidemiology of injuries, relevant anatomical considerations and prevention strategies were discussed. Results A broad spectrum of injury sites and mechanisms are seen in mountain biking, climbing or airborne sports. Mountain biking related injuries commonly involve the upper extremity, with fractures of the clavicle being the most common injury, followed by fractures of the hand and wrist. Scaphoid fractures remain of paramount importance in a differential diagnosis, given their often subtle clinical and radiological appearance. Paragliding, skydiving, and base jumping particularly affect transition areas of the spine, such as the thoracolumbar and the spinopelvic regions. Lower limb injuries were seen in equal frequency to spinal injuries. Regarding relative risk, mountain biking has the lowest risk for injuries, followed by climbing and airborne sports. Male alpinists are reported to be more susceptible to injuries than female alpinists. Generally, the literature surrounding hiking and water-related mountain sports is insufficient, and further work is required to elucidate injury mechanisms and effective preventative measures. A helmet seems to decrease the likelihood of face and head injuries in mountain sports and be a meaningful preventive measurement.